Family Ownership and Borrowing Costs in Family Businesses: The Moderating Role of Women Directors (Indonesian Journal of Digital Business, 2025)
This study aims to analyze the influence of family ownership on borrowing costs and examine the role of female directors as a moderating variable. This study uses a quantitative approach with secondary data in the form of financial statements of family businesses listed on the Indonesia Stock Exchange (IDX) for the 2019-2024 period, with a sample selection technique using purposive sampling, so that 372 observations were obtained. This study uses panel data regression analysis and moderated regression Analysis (MRA) methods. The results of the study showed that (1) family ownership had a positive and significant effect on borrowing costs, (2) female directors moderated the influence of family ownership on borrowing costs, which was proven to have a significant negative effect. The negative coefficient shows that the higher the proportion of female directors, the weaker the influence of family ownership in increasing borrowing costs. These findings indicate that the existence of female directors plays a role as quasi-moderation (pseudo-moderation) in the influence between family ownership and borrowing costs. The implications of this study show that family businesses need to strengthen governance, particularly through increasing gender diversity on the board of directors, to reduce borrowing costs and increase creditor confidence. In addition, investors and creditors need to analyze the family ownership structure along with the supervisory mechanism, as it affects the risk and cost of the loan